Disruptive Technologies and Finance Professionals Engagement: Post Covid-19 Survival Signal: Disruptive Technologies and Finance Professionals Engagement - Salawu, Mary Kehinde; Moloi, Tankiso (The Journal of Accounting and Management, 2021)
The reality of the fourth industrial revolution (4IR) has been forced on the less tech-savvy by the disruptive virus popularly known as covid-19. In this context, the responsiveness of finance professionals to job-related disruptive technology prior Covid-19 is a key indicator to their survival in the 4IR era. The study investigated the extent to which the Nigerian finance professionals engaged in online transactions prior the global pandemic. It also examined the level of ownership of digital currency both by individual finance professionals and by the organizations they work for. Quantitative data were purposively sourced from a sample of 250 accounting professionals which were selected from a population of 1300 using a structured questionnaire. Descriptive statistics and correlation analysis were employed to analyse data. In spite of the high level of engagement with online transaction, results revealed a low level of ownership of digital currency among professionals and zero level of ownership by organisations. The study signaled a low level of responsiveness to digital currency transactions, which has a high potential of displacing the service of finance professionals in the near future. The study concluded that the apathy exhibited by the finance professional prior covid-19 could deprive them the possible dividend of digital currency as a disruptive technology in the industry.